Bosnia on the border?: Republican violence in Northern Ireland during the 1920s and 1970s - Lewis, Matthew (Terrorism and political violence, 2017)
Unionist politicians have argued that Republican political violence on the Irish border, during both the partition of Ireland and more recent Northern Ireland conflict, constituted ethnic cleansing and genocide against the Protestant/Unionist community in those areas. These views have been bolstered by an increasingly ambivalent scholarly literature that has failed to adequately question the accuracy of these claims. This article interrogates the ethnic cleansing/genocide narrative by analysing Republican violence during the 1920s and the 1970s. Drawing from a wide range of theoretical literature and archival sources, it demonstrates that Republican violence fell far short of either ethnic cleansing or genocide, (in part) as a result of the perpetrators’ self-imposed ideological constraints. It also defines a new interpretive concept for the study of violence: functional sectarianism. This concept is designed to move scholarly discussion of political and sectarian violence beyond the highly politicised and moral cul-de-sacs that have heretofore characterised the debate, and has implications for our understanding of political violence beyond Ireland.